2013
DOI: 10.1177/0022034513502053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quaternary Ammonium Chain Length on Antibacterial Bonding Agents

Abstract: The objectives of this study were to synthesize new quaternary ammonium methacrylates (QAMs) with systematically varied alkyl chain lengths (CL) and to investigate, for the first time, the CL effects on antibacterial efficacy, cytotoxicity, and dentin bond strength of bonding agents. QAMs were synthesized with CL of 3 to 18 and incorporated into Scotchbond Multi-Purpose (SBMP) bonding agent. The cured resins were inoculated with Streptococcus mutans. Bacterial early attachment was investigated at 4 hrs. Biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
218
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(231 citation statements)
references
References 32 publications
13
218
0
Order By: Relevance
“…It had been suggested that DMAE-CB could be incorporated into the dental adhesive stably with better biocompatibility 52) . Besides that, Li et al 5,53) and Zhou et al 54) had incorporated new quaternary ammonium methacrylates (QAMs) with systematically varied alkyl chain lengths into SBMP bonding agent. It was found that QAM with CL16, DMADDM, had the best antimicrobial effect.…”
Section: Adhesive Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…It had been suggested that DMAE-CB could be incorporated into the dental adhesive stably with better biocompatibility 52) . Besides that, Li et al 5,53) and Zhou et al 54) had incorporated new quaternary ammonium methacrylates (QAMs) with systematically varied alkyl chain lengths into SBMP bonding agent. It was found that QAM with CL16, DMADDM, had the best antimicrobial effect.…”
Section: Adhesive Systemmentioning
confidence: 99%
“…The antibacterial effect against two E. faecalis strains (ATCC and an endodontic isolate) were assessed, and results had shown that addition of QPEI nanoparticles improved the killing ability of PCS against biofilms of both E. faecalis strains and the effects of AH Plus on the biomass of biofilms from the ATCC strain. Moreover, there were no relevant changes in physicochemical and 95) quaternary ammonium polyethyleneimine QPEI unpolymerizable composite resin 24) , endodontic materials [89][90][91] quaternary ammonium dimethacrylate QADM/IMQ polymerizable composite resin [25][26][27]32) , adhesive system 42) 2-methacryloxylethyl dodecyl methyl ammonium bromide MAE-DB polymerizable composite resin 28,29) 2-methacryloxylethyl hexadecyl methyl ammonium bromide MAE-HB polymerizable composite resin 28,29) 2-Dimethyl-2-dodecyl-1-methacryloxyethyl ammonium iodine DDMAI polymerizable composite resin 30) quaternary ammonium methacrylate QAM polymerizable composite resin 31) , adhesive system 5,53,54) 2-methacryloyloxyethyl phosphorylcholine MPC polymerizable composite resin 33) dimethylaminododecyl methacrylate DMADDM polymerizable adhesive system [43][44][45] quaternary ammonium methacrylate polymer QAMP unpolymerizable adhesive system [46][47][48] methacryloxylethyl cetyl ammonium chloride DMAE-CB polymerizable adhesive system [49][50][51][52] benzalkonium chloride BAC unpolymerizable adhesive system [55][56][57] , glass ionomer cement 73,74) , endodontic materials 87) poly-2-methacry...…”
Section: Endodontic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A quaternary ammonium dimethacrylate (QADM) was incorporated into a composite, yielding a strong antibiofilm effect [31]. Recently, a new dimethylaminohexadecyl methacrylate (DMAHDM) was synthesized and incorporated into dental resin, which showed the strongest antibacterial effect among the antibacterial monomers tested [35]. In addition, 2-methacryloyloxyethyl phosphorylcholine (MPC) was incorporated into resins to repel protein and bacterial attachment [36].…”
mentioning
confidence: 99%
“…The pH measurements were not collected from 0 h to 24 h of culture, because the planktonic bacteria in the growth medium would affect the pH values. In this way, the measured pH was only related to the biofilm adherent on the composite disk, and there was no non-adherent bacteria contribution from the medium [35,36]. The pH data were recorded once every hour from 24 h to 36 h of the incubation.…”
mentioning
confidence: 99%